Hubungan Pengetahuan Serat Dan Asupan Serat Dengan Status Obesitas Pada Remaja Di Sma Nasima Semarang - Husniati, Furi, Setyaningrum Rahmawaty, A.,M.Kes.,PhD, Ruli Sudaryanto, SST.Gz (2016)
Introduction: Obesity arises in childhood and adolescents when it continues in adulthood, it would be difficult to overcome and cause health problems in the future. Obesity can occur due to various factors, such as knowledge and nutrient intake. Objective: The research aimed to analyze the relationship between knowledge about fiber and fiber intake and status obesity of adolescents. Methods: A cross sectional study was conducted in a purposive sampling of 66 adolescents in SMA Nasima. Knowledge about fiber were obtained using questionnaires, fiber intake was measured an interview using recall during 3 day and obesity status were obtained using height and weight measurement. Analysis of the correlation was tested using Pearson and Rank Spearman. Results:Fourty eight (72,7%) adolescents had a good knowledge of fiber, sixty six (100%) adolescents had a deficit of fiber intake and fourteen (21,2%) adolescents were categorized in status of obesity (>2SD). There was no correlation between knowledge about fiber with obesity status (p = 0.423) as well as fiber intake with status of obesity (p = 0.413). 2 Conclusion: knowledge about fiber and fiber intake not always adequaly impact to status of obesity of adolescents in SMA Nasima Semarang